SOMATIC PHRASEOLOGISMS RELATING TO THE CONCEPT OF MEASURE - Shinnazarova, Saodat Zhubatkhanovna (SCIENCE and SOCIETY, 2026)
The article discusses the issue of measurative somatic phraseological units in Turkic linguistics, including Karakalpak linguistics. He paid attention to the use of mesurative somatic phraseological units in Karakalpak literary works. Explanations of their meanings are provided in phraseological dictionaries of the Karakalpak language.
Keywords: phraseology; somatism; sema; vocabulary-semantics; phonetics; component; concept; linguistic and cultural analysis; phraseological dictionary